Consumer Preferences and Demographic Influences on Watch Ownership: A Study on Wearable Technology Trends - Makhija, Hitesh; Bohra, Hussain; Seth, Dhruv; Mehta, Meet; Chauhan, Rahul; Maseleno, Andino (Greenation Research & Yayasan Global Resarch National, 2023)
This study examines the watch ownership patterns, preferences, and usage habits among individuals in Ahmedabad, with a focus on demographic factors such as age and gender. Using a sample of 106 respondents, data were analyzed to explore correlations between demographic characteristics and preferences for various watch types, including traditional, digital, and smartwatches. Results indicate that younger respondents, particularly those aged 18-25, show a strong preference for digital and smartwatches due to their multifunctional capabilities. Gender did not significantly impact watch ownership or type preference, suggesting a broadly inclusive appeal across demographics. This research highlights the shift toward multifunctional wearable technology and offers insights into the future scope of the wearables market, which is poised for further growth and adaptation. The findings contribute to a better understanding of consumer trends in wearable devices, particularly in the context of changing technological and lifestyle demands.